The Influence Of User-Generated Content To Consumer-Based Brand Equity Through Involvement In Indonesia's Top Brand Lipstic Consumer - Sunu Puguh Hayu Triono; Ratih Huriyati; Mokh Adib Sultan (Jurnal Manajemen Indonesia, 2021)
Since 2000’s content marketing began to develop and become a buzzword lately. Nowadays, content marketing is a standard practice of business and one who do not use that will be left behind. The current democratization of information is expressed mainly through User-Generated Content (UGC), so that the media model becomes more user-centric. This study attempts to discuss the effect of UGC on consumer-based brand equity (CBBE) through involvement. UGC in this study is represented through variables that motivate it, namely co-creation, empowerment, community, and self-concept. The population in this study is Top Brand lipstick consumers who have watched the UGC of those brands. Data was collected using questionnaire that distributed online and 121 data were obtained. After analyzed using SEM PLS, the results are: 1) co-creation has positive effect on involvement; 2) self-concept has positive effect on involvement; 3) involvement has a positive effect on CBBE; 4) UGC has a substantial influence on involvement; 5) UGC and involvement have a moderate influence on CBBE. Keywords— brand equity; consumer-based brand equity; content marketing; involvement; user-generated content